The association between triglyceride-glucose index, atherogenic index of plasma, systemic immune-inflammation index, and mortality in patients with acute coronary syndrome: the direct effects of glucose-lipid metabolism and U-shaped immune modulation in mortality risk - Weichen Luo; Zaixiao Tao; Xinxin Li; Yang Xu; Chun Yang; Rui Sun; Mi Wang; Zhenjun Ji; Genshan Ma (Frontiers in Cardiovascular Medicine)
BackgroundCardiovascular disease (CVD) remains the leading global cause of death, with inflammation and glycolipid dysregulation as key drivers of atherosclerosis progression. While triglyceride-glucose index (TyG) and Atherogenic Index of Plasma (AIP) are linked to cardiovascular risk, their prognostic value in Acute Coronary Syndrome (ACS) patients, particularly Acute Myocardial Infarction (AMI) patients, and mediating role of systemic inflammation remain unclear. This study investigates the relationship between glycolipid metabolism, systemic inflammation, and mortality in ACS patients.MethodsIn this single-center retrospective study, 3,861 ACS patients were analyzed. Glycolipid metabolism was assessed using the TyG and AIP index, while the systemic immune-inflammation index (SII) evaluated inflammatory status. Missing data were addressed with random forest multiple imputation. Statistical analyses included the Least Absolute Shrinkage and Selection Operator (LASSO) regression for variable selection, generalized linear modeling, restricted cubic splines (RCS) for nonlinear associations, and the Mantel test for correlations between glycolipid metabolism and inflammatory markers. Additionally, multivariable logistic regression, RCS models, and mediation analysis were used to assess associations and pathways.ResultsElevated TyG index linearly increased mortality risk in ACS patients (Odds Ratio (OR) = 1.64, 95% Confidence Interval (CI):1.07–2.52) and AMI subgroups (OR = 1.56, 95% CI:1.00–2.42), with minimal SII mediation (ACS:3.97%; AMI: non-significant).The AIP index directly increased mortality risk (ACS: Beta coefficient (β) = 0.076; AMI: β = 0.091, p < 0.001), partially offset by SII's negative mediation (ACS:−6.6%; AMI:−7.8%). SII showed U-shaped mortality associations in ACS and AMI patients, with the lowest risk around 450–900  ×  10⁹/L. Age ≥ 75 (ACS: OR = 8.35; AMI: OR = 10.12), STEMI diagnosis (ACS: OR = 1.46; AMI: OR = 1.53), and elevated total cholesterol (ACS: OR = 1.50; AMI: OR = 1.40) were independent mortality predictors. Increased HDL-C (ACS: OR = 0.198; AMI: OR = 0.280) was an independent protective factor.ConclusionThe TyG and AIP index independently predict mortality in ACS and AMI patients through direct metabolic toxicity rather than inflammatory mediation.SII exhibits a U-shaped mortality association, reflecting bidirectional immune regulation (tissue repair vs. damage), with an optimal threshold range of 450–900 × 109/L to guide anti-inflammatory strategies. Findings support metabolic-inflammatory risk stratification, prioritizing glycolipid metabolic dysregulation intervention in acute events while dynamically monitoring SII to balance immune homeostasis.Trial registrationApproved by Zhongda Hospital Ethics Committee (2020ZDSYLL164-P01); retrospectively registered.